Makna Manajemen Bagi Pengembangan Pesantren Nurul Yaqin - Yaqin, Nurul (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2015)
Managing any concept of pesantren is not an easy job, it must be remembered that there is no absolute rational concept, and most afdhal applied in pesantren. Both because of its unique growth history and because of the lack of pesantren from other social institutions in the freezing of technical activities, pesantren has not been able to manage, let alone in the matter of implementing the concept that is based on rational considerations. However systematic and methodical a concept is, at least for present generation, all such concepts will confront tremendous obstacles in its implementation.